Investigating the impact of online language exchanges on second language speaking and willingness to communicate of Chinese EFL learners: a mixed methods study - Zhou, Anju (Frontiers in Psychology, 2023)
Introduction The current study aims to investigate the impact of online language exchanges on the speaking skills and willingness to communicate (WTC) of Chinese postgraduate students in an advanced English program. The study compares two intact classes: e-tandem, who communicate with foreign English speakers through the Tandem language exchange application, and conventional, who participate in collaborative speaking tasks inside the class. The study also examines the attitudes and perceptions of the EFL learners toward the online language exchanges. Methods 58 Chinese postgraduate students were recruited from a second-year advanced English program and divided into two intact classes: e-tandem and conventional. The e-tandem group used the Tandem language exchange application to communicate with foreign English speakers online, while the conventional group participated in collaborative speaking tasks inside the class. The data were collected through the IELTS speaking module, WTC scale, and semi-structured interviews. The data were analyzed using descriptive and inferential statistics. Results Both groups showed improvement in their speaking skills and WTC. However, the e-tandem group outperformed the conventional group. The findings indicate that online language exchanges have a positive impact on the speaking skills and WTC of EFL learners. The EFL learners also had positive attitudes and perceptions toward the online language exchanges, although some expressed reservations. Discussion The study concludes that online language exchanges can be an effective tool for improving the speaking skills and WTC of EFL learners. The study also suggests that collaborative speaking courses in EFL settings should consider incorporating online language exchanges. However, the study also highlights the need to address the concerns and reservations expressed by some EFL learners regarding online language exchanges. Overall, the study has important pedagogical implications for EFL settings, suggesting that online language exchanges can enhance speaking skills and WTC.